The study of natural disasters variation (floods and droughts) in Quang Nam in the context of climate change - Lan, Vũ Thị Thu; Sơn, Hoàng Thanh (Vietnam Journal of Earth Sciences, 2013)
Located in the centre of the Middle of Vietnam, Quang Nam province is annually affected by a variety of natural disasters, including flow-related disasters such as floods and droughts, which have the most occurrence frequency, largest influence sphere and highest severity. They are also natural disasters that cause the major damage to the economy, environment and society. The forecast of aforementioned natural disasters in the context of climate change is the fundamental of proposing solutions to minimize economic, social and environmental losses, furthermore, to manage the risks of natural disasters. Based on statistical methods, the mathematical models are applied for fiting with the practice of floods and droughts that have occurred in recent years. The result of this study predicts that the occurrence of floods and droughts would increased in several subsequent years of the 21st century on the based of combination between climate change scenarios and socio-economic development planning in this area.